The Lived Experience of Male Sex Workers in Negros Oriental, Philippines - Abalos, Evalyn E. (Silliman Journal, 2022)
This study is a descriptive phenomenological inquiry that utilized the Husserlian methodology and Colaizzi’s method of data analysis to explore and describe the lived experience of male commercial sex workers (CSWs) engaged in direct sexual contact with clients and practiced unsafe sex in the province of Negros Oriental, Philippines. Seven participants, aged 18-28 years, were purposively selected to be part of the study. The unstructured in-depth interviews were guided by the main question: “Puede ko nimo istoryahan kun unsa para nimo ang kahulugan sa imong sitwasyon karon?” (“Can you please tell me the meaning of the situation in which you are in?”). Four central themes were revealed namely: struggle, realization, approval, and invulnerability. The following implications and recommendations were made in the areas of nursing practice, education, research, and health care policy: use of tele-consultation (use of phone or text messaging) to address queries of male CSWs in a confidential manner; the creation of a multidisciplinary team composed of a nurse, doctor, spiritual adviser, social worker, and a psychologist to address their concerns; information dissemination using leaflets, brochures, and educational films on sexually transmitted diseases in schools; inclusion of ‘knowing persons as caring’ in the nursing undergraduate and master’s curricula and use of this study as an example in the discussion; conduct of followup/replication studies; use of the study in the development of a middle range-theory related to the care of CSWs; and formulation of policies related to the creation of health and livelihood programs and policies on mandatory health education in private and public schools that include sex education with emphasis on safe sex practices and disease prevention.